Analysis of the competitive advantanges of UMKM in the fashion sector in Medan City using a mediator approach - Selfie Esrada Silalahi; Romindo M.Pasaribu; Nancy N.Sitompul; Sri Ida R Simanjuntak (Trigin Publisher, 2023)
The fashion sector is a factor that has the potential to support economic recovery. Problem Formulation : (1) How does marketing capability influence competitive advantage? (2) How is the influence of innovation ability on competitive advantage? (3) How does marketing ability affect competitive advantage by using the internet as a mediator? and (4) How does the ability of innovation affect competitive advantage by using the internet as a mediator?Research Objectives : To find out and analyze the effect of marketing ability on internet usage. To find out and analyze the effect of innovation ability on competitive advantage. To find out and analyze the effect of marketing ability on competitive advantage with shopping culture as a mediator variable. And to find out and analyze the effect of innovation ability on competitive advantage with shopping culture as a mediator variable.The sampling technique in this study used a non-probability sampling technique. Sampling was carried out with a single stage cluster. The number of samples or respondents in this study were 110 respondents. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS version 3 software.Results : The results of the study show that (H1) is supported or accepted, (H2) is supported or accepted. (H3) is supported or accepted, (H4) is supported or accepted, the test results show that there is a positive and significant influence between the ability of innovation on competitive advantage through the use of the internet as a mediator on the competitive advantage of UMKM in Medan city in the fashion industry is accepted